Effect of mixed-reality therapy on finger movement function of hemiplegic stroke patients - Sasaki, Shuichi; Takahira, Naonobu; Yoda, Chieko; watabe, Takayuki; Nakanishi, Risako; Aoki, Keiichiro; Miyazaki, Michiteru; Chiba, Syuhei; Kurosaki, Sora; Kobayashi, Akari (Frontiers in Virtual Reality, 2025)
Background and purposeMixed reality (MR) rehabilitation therapy tries to overcome the limitations of virtual reality therapy by integration of real, vivid images into the existing world. The aims of this study were to investigate the effect of MR therapy on finger movement function in hemiplegic stroke patients and to identify issues related to the practical use of MR system.MethodsThe study included five hemiplegic stroke patients with Brunnström stage V or lower in the upper limb or fingers. In this MR-based intervention, using HoloLens® and Leap Motion®, the unaffected hand was projected as a mirrored virtual hand onto the affected side. Patients were instructed to clench their fist on the paralyzed side ten times. The distance traveled by each fingertip between the clenched and open positions was measured using a 3D motion capture system. Additionally, a questionnaire regarding the MR therapy was administered to the patients.ResultsWearing the MR system increased the distance traveled by the tip of the index finger by a mean of 1.75 cm between the first and tenth fist-clenching movements (p < 0.05). There were no significant differences in the fingertip movement distances of any of the other fingers. The subjects gave positive reactions to most of the questions in the questionnaire.ConclusionMR therapy may help improve finger movement function in patients with hemiplegic stroke.